Abundance of Meroplankton in Inner Ambon Bay - Palinussa, Elizabeth Miklen; Ririhena, John Etry (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
The coast of Inner Ambon Bay is currently the center of economic and development activities. This can have a direct or indirect impact on the waters and the organisms in them, especially meroplankton, so the aim of the research is to calculate the abundance value of meroplankton in the waters of Inner Ambon Bay. Meanwhile, the benefits of research are as information and reference material for subsequent research related to this research. This research was conducted in June-August 2020, consisting of 5 stations (Ambang Galala-Poka, Poka, Waiheru, Passo and Halong). The method used in this research is sampling. Sampling was carried out twice a month with a research interval of 2 weeks, for 3 months. Samples were taken horizontally parallel to the coastline. Sample identification at the Pattimura University Laboratory. The results of the research found that there were 6 phylum consisting of crustacean larvae, mollusk larvae, echinoderm larvae, coelenterate larvae, annelid larvae, eggs and fish larvae. The highest meroplankton abundance in June was 1176 ind/m³ and the lowest was 490 ind/m³, in July the highest abundance was 1,253 ind/m³ and the lowest was 283 ind/m³ and in August the highest abundance was 392 ind/m³ and the lowest was 202 ind/m³. Hydrological parameters for temperature range between 25-32°C, salinity ranges between 15-31 PSU and brightness 2-13 meters.